How to Recognize, Prevent and Address Complications of Laparoscopic Gynecologic Surgery - Pramayadi, cepi T; Fani, Erliana (Indonesian Journal of Obstetrics and Gynecology, 2018)
AbstractObjective: to highlight the needs of awareness on recognizing, prevent and address complications in laparoscopic gynecologic surgery.Method: Literature reviewDiscussion: The complications of laparoscopic gynecologic surgery mainly can be classified as complications related to anesthesia, entry technique, electrosurgical, postoperative and visceral due to surgical procedure itself. Lam proposed a 6 phase-based classification of laparoscopic surgery complications; patient identification, anesthesia and positioning, abdominal entry and port placement, surgery, postoperative recovery and counselling. The aim of this classification is to promote a culture risk management to improve patient safety and outcome. Each and every phase above should be able to assessed, analyzed and executed properly to prevent complications. Conclusion: Complication in operative laparoscopy is generally minor and can be handled successfully. However, although very rare, major complications are detrimental to the patient. It also becomes heavy burden for the surgeons. Preventive measures should be implemented not only by the operator but also the anesthesiologist, and theatre practitioners. Systematic drills, which regularly re rehearsed is important in order to maintain team proficiencies. Keywords: complications, gynecologic laparoscopy, operative Laparoscopy   Abstrak Tujuan: Untuk menekankan pentingnya mengenali, mencegah dan mengatasi secara dini komplikasi operasi laparoskopi ginekologi. Metode: Kajian pustaka Diskusi : Komplikasi operasi ginekologi laparoskopi dapat diklasifikasikan menjadi komplikasi yang berhubungan dengan anestesi, teknik masuknya trokar utama, terkait elektro surgikal, komplikasi pascaoperasi dan komplikasi visera (pembuluh darah, usus, cedera traktus urinarius) terkait tindakan operasi itu sendiri. Lam mengusulkan suatu klasifikasi berbasis fase, antara lain, identifikasi pasien, anestesi dan posisi pasien, akses masuk abdomen dan penempatan trokar, terkait operasi, pemulihan pascaoperasi dan konseling. Tujuan dari klasifikasi ini adalah untuk meningkatkan budaya sadar risiko,guna meningkatkan keselamatan pasien. Setiap tahap harus dapat dilaksanakan, dinilai dan dianalisis dengan baik untuk mencegah terjadinya komplikasi. Kesimpulan: Komplikasi pada operasi ginekologi laparoskopi umumnya ringan dan dapat ditangani dengan baik. Walaupun jarang terjadi, komplikasi berat umumnya sangat merugikan pasien dan menjadi beban operator. Langkah-langkah pencegahan ini harus dilaksanakan oleh operator, tim anestesi serta seluruh tim kamar operasi. Simulasi  harus dilaksanakan, guna mempertahankan kecakapan tim Kata kunci : komplikasi, laparoskopi ginekologi, laparoskopi operatif